Inhibition by Thyroid Hormones of Cell Migration Activated by IGF-1 and MCP-1 in THP-1 Monocytes: Focus on Signal Transduction Events Proximal to Integrin αvβ3 - Candelotti, Elena; De Luca, Roberto; Megna, Roberto; Maiolo, Mariangela; De Vito, Paolo; Gionfra, Fabio; Percario, Zulema Antonia; Borgatti, Monica; Gambari, Roberto; Davis, Paul J.; Lin, Hung-Yun; Polticelli, Fabio; et al. (Frontiers in Cell and Developmental Biology, 2021)
Interaction between thyroid hormones (THs) and the immune system is reported in the literature. Thyroid hormone (THs), thyroxine, T4, but also T3 act nongenomically through mechanisms that involve a plasma membrane receptor αvβ3 integrin, a co-receptor for Insulin-like growth factor-1 (IGF-1). Previous data from our laboratory show a cross-talk between THs and IGF-1 because THs inhibit the IGF-1-stimulated glucose uptake and cell proliferation in L-6 myoblasts and the effects are mediated by integrin αvβ3. IGF-1 also behaves as a chemokine, being an important factor for tissue regeneration after damage. In the present study, using THP-1 human leukemic monocytes, expressing αvβ3 integrin in their cell membrane, we focused on the cross-talk between THs and either IGF-1 or monocyte chemoattractant protein-1 (MCP-1) studying cell migration and proliferation stimulated by the two chemokines, and the role of αvβ3 integrin, using inhibitors of αvβ3 integrin and downstream pathways. Our results show that IGF-1 is a potent chemoattractant in THP-1 monocytes stimulating cell migration and thyroid hormone inhibits the effect through αvβ3 integrin. Thyroid hormone also inhibits IGF-1-stimulated cell proliferation through αvβ3 integrin, an example of a cross-talk between genomic and nongenomic effects. We also studied the effects of Thyroid hormone on cell migration and proliferation induced by MCP-1, together with the pathways involved, by a pharmacological approach and docking simulation. Our findings show a different downstream signaling for IGF-1 and MCP-1 in THP-1 monocytes mediated by the plasma membrane receptor of THs, integrin αvβ3.